2015
DOI: 10.1074/jbc.m115.653303
|View full text |Cite
|
Sign up to set email alerts
|

Combined Crystal Structure of a Type I Cohesin

Abstract: Background: Cellulosomal cohesin-dockerin types are reversed in Bacteroides cellulosolvens. Results: Combined crystallographic and computational approaches of a lone cohesin yielded a structural model of the cohesindockerin complex that was verified experimentally. Conclusion: The dockerin dual-binding mode is not exclusive to enzyme integration into cellulosomes; it also characterizes cell-surface attachment. Significance: This combined approach provides a platform for generating testable hypotheses of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Previous research suggested that a dual-binding mode of the dockerins would result in increased flexibility characteristics of the catalytic subunits [ 67 , 68 ], it was reported previously that the type I ScaA dockerin has a dual-binding mode in the recognition of the B. cellulosolvens type I cohesins [ 69 ]. The additional type I dockerins reported here share similar binding preferences and sequence similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggested that a dual-binding mode of the dockerins would result in increased flexibility characteristics of the catalytic subunits [ 67 , 68 ], it was reported previously that the type I ScaA dockerin has a dual-binding mode in the recognition of the B. cellulosolvens type I cohesins [ 69 ]. The additional type I dockerins reported here share similar binding preferences and sequence similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Three other PPIs showed no leakiness in the absence of one of the interaction partners, and at the same time showed a significant induction of SEAP when both parts were expressed in the same cell to reconstitute a functional TF ( Figure 1 c,d). These included (i) cohesin-dockerin proteins from Acetivibrio cellulolyticus (Coh(Ac)/Doc(Ac)), 21 (ii) antiparallel leucine zipper (Zip – /Zip + ) 22 domains from an engineered, bipartite TF used for gene control in Caenorhabditis elegans and (iii) the SunTag system (scFv(G4)/G4) 23 based on a single chain variable fragment of an antibody that specifically binds a yeast-derived 19 amino acid peptide. We observed no crosstalk between the different parts of the protein–protein interactions, which is required for their further assembly to multipartite TFs ( Figure 1 e).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recent reports revealed that the attachment of cellulosomes to the P . cellulosolvens 21 and A . cellulolyticus cell surface is also mediated by Docs that display a dual-binding mode 17 , 22 .…”
Section: Discussionmentioning
confidence: 99%